(untitled) (Journal of Science and Technology, 2016)
To contribute to the sparse information on dimensional variations of umbilical cords in Ghana, 124 placentae with attached umbilical cords were studied. The placentae were obtained from the University of Science and Technology Hospital between 2000 and 2002. Average cord length was 47.04cm (SD 12.8cm) with the shortest cord being 5.5cm and the longest 75.50cm. By empirical definition, 21.56% of the cords were Short whereas, 78.44% were long. Most of the umbilical cords (63%) had empirically eccentric attachments to their placentae; 20.48% had central and 16.52% had marginal attachments respectively. Occurrence of furcate insertion of umbilical cord vessels into the placenta was 28% and non-furcate insertion was 72%. These quantitative data provide baseline values for further investigation.